Innovations in insuring the poor: Microfinance and unexpected consumption expenditures - Hornbeck, Richard (International Food Policy Research Institute, 2009)
Questions in development economics often focus on the poor’s limited access to capital and, in particular, on their high interest rate for borrowing. Despite this high price for capital, many poor households borrow substantial amounts for production and consumption. This situation suggests that the poor have access to very productive investment opportunities and face periods when they have a very strong desire to consume more than their current income. This brief explores the role of microfinance in paying for unexpected consumption expenditures. Motivated by high borrowing costs among the poor, a large number and wide variety of organizations have made efforts to expand the availability of credit and decrease interest rates. Microfinance organizations are one prominent example, and loans are often also provided by banks, moneylenders, family, friends, and other local associations. Households also finance major expenditures using cash savings, funds from rotating savings groups, the sale or pawning of household items, insurance or entitlement programs, or gifts. Indeed, financial diaries show that the poor simultaneously use a large number of formal and informal financial instruments. It is not clear whether this large number of financial instruments represents an economic success or failure. Assuming that the poor are not simply tricked, each of these instruments is fulfilling some demand that is not met by the other instruments. This reflects a great deal of adaptability in creating and adopting different instruments, but it also reflects the limited capabilities of each particular instrument individually. Even when each source can supply only a limited amount of capital, borrowers often do not use them to the fullest extent possible, despite seemingly substantial overlap in the services provided by each instrument. Encouraging the creation of new financial instruments to cover unmet demands is a patchwork solution to these problems. It would be useful to understand what underlying rigidities prevent some products from substituting for others. Such an understanding would both help in developing new instruments and potentially allow for more direct corrections to the underlying financing challenges faced by the poor. For example, for unexpected consumption expenditures, there is an inherent importance in having fast access to funds. If a household member experiences a sudden illness, accident, or pregnancy complication, receiving immediate hospital care will often require substantial upfront payments. Microfinance clients may be able to obtain funds on a regular schedule for business investments, but not necessarily for immediate health expenditures.